Effect of reject temperature on aerospace pulse tube refrigerator. (April 2023) - Zhang, Ankuo; Han, Yinan; Guo, Shuling; Tong, Renchao
Highlights: The influence of the reject temperature on the PTR performance is investigated. Analyzed the effect of reject temperature on compressor impedance, phase and losses. Experimental results are in agreement with simulated values. Abstract: Pulse tube refrigerators (PTRs) have significant potential application prospects for space infrared detection. Currently, the third-generation detection technology is a developing trend in the large array focal plane field, which requires the PTR to provide higher cooling capacity for the infrared detector by increasing the input power and heat dissipation. Owing to the vacuum environment present in orbit, the temperature of the working environment becomes more extreme, particularly for coaxial PTRs. In this study, the effect of reject temperature on the cooling performance of a coaxial PTR was systematically investigated, and some parameters are analyzed, such as compressor impedance, phase shifts, main losses, enthalpy flow, mass flow, and input power with reject temperature. As the reject temperature increases, the phase at each position in the PTR will exhibit different degrees of hysteresis, and there will be less loss of major components and decreased enthalpy flow at the cold end of the pulse tube. In addition, an experimental study on the adaptability of the PTR with different cooling temperatures to the reject temperature was performed. In the experiment, when the reject temperature increases from −40 °C to 40 °C, the input electrical power required for PTR with a cooling capacity of 4 W@60 K increases from 106 W to 193 W. The experimental results are consistent with the simulated values.